An Endeavour for Autonomy: How Girls Understand Their Lived Experiences of Being Referred to Secure Care. (February 2018) - Andersson Vogel, Maria
In discussion of troubled adolescent girls, their mental health often is in focus and a discourse constructing girls as vulnerable victims therefore dominates Swedish social services and secure care. This article is an investigation of how the girls themselves are navigating the discursive terrain where understandings of troubled adolescent girls in secure care are regulated. The results show that even though the girls' stories show considerable similarities with what is previously known about troubled adolescent girls, their understandings of their lived experiences differ. The girls resist the dominating discourses that view them as victims by emphasizing their autonomy and own responsibility. However, in trying to distance themselves from devaluing interpretations, they take an attitude that ultimately obstructs their possibilities of getting help, since it inevitably puts them in opposition to the care system.